2020
DOI: 10.1038/s41598-020-70366-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Wilson disease mutations revealed that interactions between different ATP7B mutants modify their properties

Abstract: Wilson disease (WD) is an autosomal-recessive disorder caused by mutations in the copper (cu)transporter ATP7B. Thus far, studies of WD mutations have been limited to analysis of ATP7B mutants in the homozygous states. However, the majority of WD patients are compound-heterozygous, and how different mutations on two alleles impact ATP7B properties is unclear. We characterized five mutations identified in Indian WD patients, first by expressing each alone and then by co-expressing two mutants with dissimilar pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(62 reference statements)
0
21
0
Order By: Relevance
“… 18 , 25 Several reasons are likely to contribute to this difference including the presence of more than 600 pathogenic or likely pathogenic variants in ATP7B, 10 difference in the severity of certain variants e.g. truncating variants that lead to a significant decrease in the protein vs. missense changes, and also the combination of variants in either homozygous or compound-heterozygous states, 26 new classification criteria for assessing pathogenicity of variants, 27 variation in penetrance of certain variants, 11 the potential for epigenetic mechanisms of gene expression regulation causing clinical disease 28 and the likeliness of undiagnosed cases being missed in clinical prevalence studies. 29 …”
Section: Discussionmentioning
confidence: 99%
“… 18 , 25 Several reasons are likely to contribute to this difference including the presence of more than 600 pathogenic or likely pathogenic variants in ATP7B, 10 difference in the severity of certain variants e.g. truncating variants that lead to a significant decrease in the protein vs. missense changes, and also the combination of variants in either homozygous or compound-heterozygous states, 26 new classification criteria for assessing pathogenicity of variants, 27 variation in penetrance of certain variants, 11 the potential for epigenetic mechanisms of gene expression regulation causing clinical disease 28 and the likeliness of undiagnosed cases being missed in clinical prevalence studies. 29 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the two frequent core promoter polymorphisms are candidate genetic modifiers of Wilson disease phenotype. The marked variability of the Wilson disease clinical phenotype that is even observed in carriers of the same mutation(s) has not yet been explained; several modifying influences have been suggested to contribute: besides environmental factors, epigenetic and transgenetic effectors and protein interactions of different missense variants are in the list 40 , 43 , 44 .…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, Roy et al characterised the functional properties of further variants demonstrating differential effects on intracellular copper concentrations. 18 Intriguingly, they also found that co-expressing the G1061E variant, which is usually retained in the ER, with the A595T variant restored localisation of ATP7B to the TGN. ATP7B has previously been shown to form stable dimers in vitro and so genetic and functional studies may need to consider interactions between heterozygous variants in the future.…”
Section: Molecular Mechanismsmentioning
confidence: 92%